Report of the Advisory Group on Tax Policy and Tax Administration for the Tenth Plan - Planning Commission (Planning Commission, 2001)
The necessary stance of the authorities in the area of tax policy and tax administration for the Tenth Plan comprises many facets. For central taxes, the potential of corporation and personal income taxes—that have demonstrated the highest revenue buoyancy—has to be tapped further. Measures include improvements in the tax structure as well as in tax administration.
Planning Commission Government of India
Planning Commission Government of India